Analyzing Language Attitude of Javanese and Sundanese Urban Community on English Language Pedagogy, In Indonesia - Setyo Wati (Qubahan Academic Journal)
Language attitude in foreign language pedagogy becomes an interesting discussion, especially in English language teaching learning process. Teachers and learners are the importance of teaching learning process, including the language attitude in the pedagogical process. Due to the importance of the language attitude, this paper sheds to describe the language attitude of English learners from Javanese and Sundanese urban community. Respondents in this research involved were 214 respondents living in Surakarta city, 85 respondents living in Tasikmalaya city. This study seeks to discover how Javanese and Sundanese people use their language in learning English. This research employed a mixed method research design to collect, analyze, and to mix both quantitative and qualitative data in a single study. Researcher used theory in a quantitative study to provide an explanation about the relationship among variables in the study. Thus, it is essential to have grounding in the qualitative study. The results of the study are as follows. There is a different attitude showed by Javanese and Sundanese people, in terms of cognitive, behavioral, and affective aspects of language attitudes towards English. The attitudes of male Javanese people towards English were higher than that of female ones indicating more positive attitudes towards English. On the other hand, the attitudes of male and female Sundanese people towards English were equally low. Notwithstanding, the attitudes of female Sundanese people towards English are slightly higher than male ones.